Jovens expostos à violência intrafamiliar e percepções sobre a escola: um estudo comparativo - Ferreira, Carlos Magno do Carmo (2018)
Violence against children and adolescents and their consequences in the school process has attracted a growing interest from educators, educational psychologists and health professionals. However, there is a small number of research in the educational area. This study investigated the relation between school sense and victimization in various types of violence, such as: urban violence, neglect of caregivers and those responsible and mistreatment suffered by children and adolescents in their family context. Interfamily violence against children and adolescents is classified according to the way it is practiced, the type of author who practices it and the place of practice. The situations of psychosocial risk have provoked the growth of violence. This is a quantitative approach research, which used the database of the National Survey on Risk Factors and Protection of Brazilian Youth, carried out in six Brazilian capitals and in the Federal District. The database is comprised of 109 multiple choice questions that were answered by 7482 young high school students and used to investigate aspects of various topics. This study selected and investigated the perception of 446 young teenagers who declared themselves exposed to interfamily violence on the meaning of school in their lives and compared with the perception of those 1141 young teenagers who declared themselves not exposed to this violence. Results emphasize the importance of family and school as part of a safety net for children and adolescents. The study indicates that young people exposed to interfamily violence they missed more school days, almost half came to disapproval, negatively assessed the level of confidence in school, were disadvantaged in studying in public school and had a negative view of liking going to school. The study also indicated that exposure to interfamily violence does not constitute a probable factor for the youngster to give importance to the study in the present and in the future. The results show that young people exposed to violence have confidence in school friends and that despite their distrust of teachers, they trust the school institution, but little more than half believe they have the conditions to enter university. The college is classified with high importance in the personal fulfillment, but they think that only through the education of the private network they can enter the university. The study emphasized the importance of family, school and social networks formed by people with high significance as subjects that can positively interfere in the formation of a protection network, in the development of children and adolescents and indicating them as inducers of resilience.